Fauna of Ixodic Ticks and Dynamics of Their Seasonal Activity in the Context of Altitudinal Zonation of Dagestany - A. M. Ataev; M. M. Zubairova; N. T. Karsakov; Z. M. Dzhambulatov (Российский паразитологический журнал, 2019)
The purpose of the research is to study the current status of fauna of ixodic ticks in the context of altitudinal zonation of Dagestan and the dynamics of their seasonal activity.Materials and methods. Collection of ixodic ticks of cattle and sheep was carried out during 2002-2017. Total 11580 ixodids had collected. Differentiation of ticks was conducted according to indicators.Results and discussion. 22 species of ixodic ticks were found on animals in flat, submontane and mountain belts of Dagestan: Ixodes – 2, Hyalomma – 6, Boophilus – 1, Dermacentor – 3, Rhipicephalus – 5, Haemaphysalis – 5. Such species of genus as Boophilus, Hyalomma, Dermacentor are predominate inixodids fauna. B.annulatus, R.bursa, D. dagesthanicus, H. scupense is registered in mountain belt.